2020
DOI: 10.1093/abbs/gmaa101
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin induces ER stress-dependent apoptosis of protoscoleces

Abstract: In this study, we investigated the effect of dihydroartemisinin on Echinococcus protoscoleces and explored the role of endoplasmic reticulum stress in this process. Echinococcus protoscoleces were collected and cultured in RPMI 1640 medium. Changes in the expressions of glucose-regulated protein 78 (GRP-78), caspase-12, and C/EBP homologous protein (CHOP) were assessed through confocal immunofluorescence and western blot analysis. Cell viability and morphological changes were observed under a light microscope.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Caspase‐3 is a biomarker of cell apoptosis and plays a vital role in this process. Compound 31 was found to increase caspase‐3 activity, demonstrating its ability to induce apoptosis on Echinococcus protoscoleces (Ma et al., 2020). These findings suggest that these compounds have harmful effects on parasites, causing damage and changes in their structure.…”
Section: Mechanisms Of Action Of Natural Terpenes Against Echinococcu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Caspase‐3 is a biomarker of cell apoptosis and plays a vital role in this process. Compound 31 was found to increase caspase‐3 activity, demonstrating its ability to induce apoptosis on Echinococcus protoscoleces (Ma et al., 2020). These findings suggest that these compounds have harmful effects on parasites, causing damage and changes in their structure.…”
Section: Mechanisms Of Action Of Natural Terpenes Against Echinococcu...mentioning
confidence: 99%
“…Compound 31 also caused a loss of hooks in protocoleces, as well as the destruction of microtrichia and the development of lipid droplets. (Fabbri et al, 2018;Liu et al, 2021;Ma et al, 2020). Ultrastructural analysis of E. granulosus cysts indicated that after 2 days of incubation with 73.40 μM compound 30, the germ layer suffered severe damage.…”
Section: Alterations In the Tegumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of dihydroartemisinin, another anti-malarial drug, resulted in the morphological changes and loss of viability of protoscoleces. It induced apoptosis by endoplasmic stress-caspase3 pathway in vitro (Ma et al 2020). Artesunate is responsible for damaging the DNA of metacestodes and protoscoleces of E. granulosus and this damage is provoked by oxidative stress (Wen et al 2020).…”
Section: Anti-malarial Drugsmentioning
confidence: 99%
“…Although the number of PSCs was different in different hydatid cysts, the ES concentration was not the main research subject in our experiment, so in this experiment, we only used 100% ES. In terms of experimental design, different from the previously published randomized design [24], we adopted a factorial experimental design method, taking ES and time as two independent variables. In this way, we could not only observe the main effect of ES but also elucidate the interaction between ES and time, which greatly reduced the experimental error.…”
mentioning
confidence: 99%